A new Epstein-Barr virus transactivator, R, induces expression of a cytoplasmic early antigen. - Hardwick, J M (1988)
Several Epstein-Barr virus (EBV) early promoters respond to a new EBV transactivator encoded by BRLF1, designated R. Transactivation was measured in chloramphenicol acetyltransferase assays on Raji, BHK, and Vero cells that were cotransfected with the transactivator and target promoters linked to the cat gene. The divergent promoter of BamHI-H was particularly responsive to R transactivation. This large promoter region consists of a leftward TATA box for the NotI repeat gene (BHLF1) and a probable rightward TATA box for the EA-R gene (BHRF1) separated by 940 base pairs of unusual sequence complexity. Sequences within this divergent promoter region appear to confer inducibility by EBV transactivators R and Z (BZLF1). The Z transactivator stimulated expression in both the leftward and rightward directions, and R stimulated expression primarily in the rightward direction, but the MS transactivator (BMLF1) had no activity in either direction. The adenovirus E3 promoter also responded to the R transactivator, but several other herpesvirus and human promoters were nonresponsive. When the divergent promoter was linked to the EA-R gene as it is in the EBV genome, the R and Z transactivators also induced the expression of EA-R in cotransfected cells. This cytoplasmic early antigen is encoded by BHRF1 and may be anchored in intracellular membranes by a carboxy-terminal transmembrane region.